Solar energy application for mosque in Perak: the case study of Ar-Rahmaniah mosque at Kampung Pengkalan Baharu, Perak / Nur Sahida Rahman, Nur Azfahani Ahmad and Sabarinah Sheikh Ahmad - Rahman, Nur Sahida; Ahmad, Nur Azfahani; Sheikh Ahmad, Sabarinah (2021)
Malaysians use electricity generated from non-renewable fossil fuel every day and are unaware of the situation that these resources are actually decreasing and depleting due to its rapid consumption. This is due to the rapid development of Malaysia that leads to heavy consumption of electricity in their lifestyle. In addition, the lack of knowledge of these people on the importance of renewable energy that can act as supplement power for electricity. People are also unaware of global warming issues and carbon footprints produced due to electricity generation. Frequent blackouts can also occur in the future if the non-renewable resources deplete. It also can happen to many Mosques in Malaysia which use main power supply for conventional electricity. Therefore, it is necessary to find a solution to overcome this situation by using renewable energy. The most accessible renewable energy that can be harnessed in Malaysia is solar energy. Therefore, it is wise to propose a sustainable energy consumption for Mosques in Malaysia which is based on the application of solar energy. The aim of this research is to explore the establishment of solar energy application as a supplement energy for electricity for Mosques in Perak, Malaysia. The focus of this study is to encourage people in Malaysia to use energy generated from solar energy. Mosques are among the important buildings which symbolises the local community in Perak. Therefore, it is significant to implement solar energy application for this Mosque. This research intends to assist communities in Perak Malaysia to obtain a sustainable lifestyle from the Mosque significant building that we have in Malaysia.